KAJIAN YURIDIS PERTANGGUNGJAWABAN PIDANA TERHADAP TINDAK PIDANA PEMALSUAN ASAL USUL PERKAWINAN - Merina Kusumawati; Sigit Setyadi (Kajian Hasil Penelitian Hukum, 2017)
The Government has explicitly regulated marital matters in the provisions of laws and regulations, namely Law Number 1 Year 1974 on Marriage. Violations of the criminal provisions governing the prohibition of falsifying the marriage principle are quite prevalent. The increase in the number of complaints, indicating the increasing awareness of the women victims to report the case, while the number of violations is estimated to be many, but because of the incomprehension of the victims and the reluctance to deal with the law resulted in the reports being found not too large. Criminal liability concerning criminal act of counterfeiting of marriage origin is imposed on the perpetrator based on no criminal principle without error.Keywords : Criminal liability, Forgery, Marriage